Analyzing The Sustainability Of High Quality Arabica Coffee Farming Busnesses In The Municipalities Ainaro, Emerera And Liquica District Of Timor Leste - Marcal Gomes, Lucio; Jesus Gomes, Julio de (Jurnal Syntax Fusion, 2024)
Arabica coffee is the most critical plantation product for Timor-Leste. It is sold on regional, national and international markets to provide income and foreign exchange to rural areas. This study aims to analyze the sustainability of coffee cultivation from an economic perspective. Specifically, we compared the income levels of certified and non-certified coffee farmers and the level of participation in farmer group activities between certified and non-certified coffee farmers. We achieved this through Arabica coffee growers (Coffea Arabica L.). Analyze the indirect benefits. The research site was selected by purposive Sampling, considering that most of the livelihoods of residents in the region are coffee farmers. The study was conducted from July to December 2022. This type of research is descriptive with a quantitative approach. The number of samples used was 180 respondent farmers calculated using the Slovin formula so that the number of pieces for certified and non-certified farmers in each region was 30 people, with the sampling technique used purposive Sampling. The analytical method used in this study is qualitative and quantitative descriptive analysis. The data processing method is performed by tabulation and classification on Microsoft Excel software. The results show that the income of certified coffee growers is higher than that of uncertified households. The income obtained by certified coffee farmers amounted to $748.03 per hectare, and B/C amounted to 1.57 for the participation rate. Certified coffee farmers are more active in group activities than non-certified ones, with the highest participation rate in the Ermera district area. Indirect revenue obtained by coffee farmers comes from the value of carbon storage, with an average contribution value ranging from $85.28-98.90 or equivalent to 54.35-82.92% of the total revenue per hectare